30+3*x-2*(12-x)=38

Simple and best practice solution for 30+3*x-2*(12-x)=38 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 30+3*x-2*(12-x)=38 equation:


Simplifying
30 + 3x + -2(12 + -1x) = 38
30 + 3x + (12 * -2 + -1x * -2) = 38
30 + 3x + (-24 + 2x) = 38

Reorder the terms:
30 + -24 + 3x + 2x = 38

Combine like terms: 30 + -24 = 6
6 + 3x + 2x = 38

Combine like terms: 3x + 2x = 5x
6 + 5x = 38

Solving
6 + 5x = 38

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + 5x = 38 + -6

Combine like terms: 6 + -6 = 0
0 + 5x = 38 + -6
5x = 38 + -6

Combine like terms: 38 + -6 = 32
5x = 32

Divide each side by '5'.
x = 6.4

Simplifying
x = 6.4

See similar equations:

| 10-2m=m+4 | | 8y-7=14y+23 | | 4x+12=38 | | -6x^2=-35 | | 10/62 | | 9x-7=6x+38 | | 50=x-15 | | 27x+901= | | 8x-3=5x-57 | | n/4-5=17 | | 5(x+6)-(x+28)=-2x | | f(x)=x-9/X^2-16 | | 8x+2=6x+36 | | 8(3x-4)=14x-2 | | 17x-9x=24 | | 5x-(2x+9)=9 | | -97x+42x= | | 6(7x-6)=27 | | 15-6x=-51 | | c+1.7=2.6 | | 96-3x=8 | | -6i+4= | | 6x-17=-107 | | 5(x-6)-(x+28)=-2x | | (x-3+5i)(x-3-5i)=0 | | 420=(2x+5)x | | 3(5-2m)=27 | | 798x+2(60)=500x | | 3.4+t=10.5 | | 5x+15=3+7x-8 | | 3y+9y=21 | | 3c+15=90 |

Equations solver categories